Lattice Boltzmann model for thermal free surface flows with liquid-solid phase transition - Attar, Elham; Körner, Carolin (International Journal of Heat and Fluid Flow, 2011)
Purpose: The main objective of this work is to develop an algorithm to use the Lattice Boltzmann method for solving free surface thermal flow problems with solid/liquid phase changes. Approach: A multi-distribution function model is applied to simulate hydrodynamic flow and the coupled thermal diffusion-convection problem. Findings: The free surface problem, i.e. the reconstruction of the missing distribution functions at the interface, can be solved by applying a physical transparent momentum and heat flux based methodology. The developed method is subsequently applied to some test cases in order to assess its computational potentials. Practical implications: Many industrial processes involve problems where non-isothermal motion and simultaneous solidification of fluids with free surface is important. Examples are all castings processes and especially foaming processes which are characterized by a huge and strongly changing surface. Value: A reconstruction algorithm to treat a thermal hydrodynamic problem with free surfaces is presented which is physically transparent and easy to implement. © 2010 Elsevier Inc.
Keywords: Fluid dynamics; Free surface; Heat transfer; Lattice Boltzmann method; Solidification